O blog como ambiente digital de difusão de prática pedagógica para professores alfabetizadores - Paulo, Agatha Eleuterio (2020)
Digital technologies are present in the teacher's daily routine, whether in early childhood education, elementary education or in higher education, and their use requires certain skills both in the handling of the technological instrument, as well as in reading and writing. When faced with the multimodality of texts in a digital environment, the teacher has to mobilize some knowledge regarding the digital environment. Such knowledge can contribute to significant changes in teaching practices at the school level. Thus, this research starts from the premise that the literacy teacher uses digital technologies in search of subsidies for his work in the classroom, opting for various digital resources that offer suggestions for literacy activities available online. Among many, we chose blogs, as it is an easily accessible portal available in the digital environment, being common in the educational environment as a research tool for planning activities by teachers. Therefore, this study aims to analyze a blog focused on literacy, with the purpose of describing the structure, the pedagogical proposals offered and reflecting on the imposition of a certain level of digital literacy for its use. For this, we use the qualitative approach for a descriptive and exploratory research, conducting a survey of the same open and free, aimed at literacy, as an analysis procedure we chose the content. The theoretical principles were based on the studies of Marcuschi (2002), Soares (2009), on literacy and digital literacy, of Rojo (2009), on multiliteracy, Lévy (1999) and Chartier (2002) on reading and writing in environments among other authors who speak on the themes. The results of the research indicate that the blog shows itself to be a digital environment that is not only constituted by the blogger's particular convictions, but that corresponds to the expectations and needs expressed by teachers, who through shared dialogues, comments, activities, planning and challenges , establish a digital community for the dissemination of pedagogical practices.